Penguatan pendidikan karakter berbasis kearifan lokal Mandar Metabe' dan Mepuang di SDN 001 Campalagian - Hartiwisidi, Nurcahya; Damayanti, Eka; Musdalifah, Musdalifah; Rahman, Ulfiani; Suarga, Suarga; Shabir U, M (Directorate of Research and Community Service, Universitas Negeri Yogyakarta, 2022)
This study aims to strengthen character education based on the local wisdom of Mandar Metabe' and Mepuang at State Elementary School 001 Campalagian Polewali Mandar, West Sulawesi. Researchers try to examine more deeply the management of programs that have been made starting from planning, implementation, and evaluation. This research is a qualitative descriptive study with an ethnographic approach and was compiled using primary and secondary data. In this study, researchers used the concept of local wisdom of Mandar culture and character education strengthening programs in linking existing theories and facts. Through this research it can be seen that there are four programs of character education strengthening compiled by SDN 001 Campalagian which are carried out through learning methods and routine activities (habituation), namely (1) one day speaking Mandarin, (2) greeting the teacher with the nickname Puang as a form of habituation of respecting elders, (3) integration of local wisdom material which is carried out during the learning process by inserting local wisdom material such as the virtues of Metabe' and Mepuang, and (4) ibda' bi nafsika which means starting from oneself which is done by giving examples of commendable behavior from the teacher towards students.